KESEDIAAN MEMBAYAR KONSUMEN TERHADAP PRODUK PISANG CAVENDISH DI TOKO RITEL MODERN KOTA SURABAYA - Mirza Andrian Syah; Meimy Ratnakanyaka (Jurnal Ilmiah Sosio Agribis, 2023)
The research aimed to determine the willingness to pay of consumers for Cavendish banana products in modern retail stores in Surabaya. The study was conducted from June to August 2023 in several modern retail stores in Surabaya with a total of 200 respondents selected using the Accidental Sampling technique. Data analysis was performed using the Contingent Valuation Method. The research findings indicated that 33% of the respondents were willing to pay more for Cavendish banana products, characterized by having a monthly expenditure between IDR1,000,000 – IDR2,500,000, a high level of education, employment as civil servants/private sector employees, and a lifestyle that prioritizes healthy food choices. The maximum average Willingness To Pay (WTP) value was IDR22,549 or 2.49% higher than the selling price of Cavendish bananas during the study, which was Rp22,000/kg. The higher WTP value suggests that the selling price of the product in modern retail stores was already quite affordable.Keywords: willingness to pay, consumers, cavendish banana, modern retail.